Yiai Fuzheng decoction inhibits triple-negative breast cancer by remodeling the immune microenvironment - Yu, Chaochao; Jia, Chengqian; Chen, Guopeng; Li, Yi; Liu, Yixin; Zhang, Yingwen (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to examine the potential anticancer properties of Yiai Fuzheng decoction (YFD), along with its mechanism of action against triple-negative breast cancer (TNBC).MethodsA TNBC mouse model was established by inoculating 4T1 cells into the 4th mammary fat pad. Micropositron emission tomography (micro-PET), hematoxylin and eosin (HE) staining, immunohistochemistry, immunofluorescence assays, flow cytometry, and western blotting were used to assess the therapeutic effects of YFD. The components of YFD were identified via UHPLC-Q/Orbitrap MS. Nontargeted metabolomic analysis was performed to identify changes in tumor metabolites via gas chromatography-time-of-flight mass spectrometry (GC-TOF/MS). The Illumina sequencing platform was used to identify differentially expressed genes in the tumors.ResultsA total of 20 bioactive components of YFD were screened and identified. We found that YFD treatment resulted in a substantial increase in CD4+ and CD8+ T cells, a reduction in myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs), and an increase in the M1/M2 ratio of TAMs in tumors. These changes create a tumor-suppressive microenvironment that inhibits tumor growth and metastasis in TNBC mice. YFD can affect various immune regulatory pathways, such as inactivation of the mitogen-activated protein kinase kinase/extracellular signal-regulated kinase 1 and 2 (MEK/ERK1/2) pathway. Additionally, metabolomic analysis suggested that YFD could reprogram several altered metabolic pathways, including the urea cycle; metabolism of arginine and proline; pyruvate; the Warburg effect; D-arginine; and D-ornithine, glutamate, glycine, serine, and tryptophan, to suppress cancer progression.ConclusionOur findings provide preclinical evidence that supports the application of YFD in TNBC treatment.